Study on the Influence of Flat Heat Pipe Structural Parameters in Battery Thermal Management System - Wang, Yueqi; Dan, Dan; Xie, Yi; Li, Weifeng; Guo, Hongqiang; Zhang, Yangjun (Frontiers in Energy Research, 2022)
Battery performance and lifespan are greatly dependent on its temperature, and a good battery thermal system (BTMS) can make the battery work at its favorable temperature range, improve its electrical performance, and extend its lifespan. Due to the high heat conductivity and large surface area of flat heat pipe (FHP), the FHP-based BTMS can quickly remove the heat produced by the battery and improve the temperature homogeneity among cells in the pack. In this study, the FHP is applied to the BTMS, and the influence of its structure on the battery thermal dynamics is studied. Firstly, a coupled thermal model for the FHP-based BTMS is established and verified by the experiment. This model integrates the resistance-based thermal model of the battery and FHP model based on the thermal resistance network. Then, the effect of the structure parameters of FHP such as the thickness, porosity, and particle diameter of sintered wick on the thermal performance of the battery is investigated. According to the results, the temperature variation among battery cells rises significantly when the dimensionless thickness of the wick is greater than 0.7. Moreover, the change of the porosity and particle diameter of the wick results in a nonlinear development of the wick thermal resistance which finally changes the heat conductivity of the FHP and battery temperature. Finally, a neural network model (NNM) is used to establish the relationship between the FHP parameters and battery thermal performance for optimizing the BTMS structure. According to optimization result, the optimized FHP can keep the maximum battery temperature below 40°C at a discharge rate of 2C and reduce the temperature variation in the battery by 7.4%.